Appraisal of postbiotics in cancer therapy - Sudaarsan, Aruna Senthil Kumar; Ghosh, Asit Ranjan (Frontiers in Pharmacology, 2024)
Cancer remains a multifactorial disease with an increased mortality rate around the world for the past several decades. Despite advancements in treatment strategies, lower survival rates, drug-associated side effects, and drug resistance create a need for novel anticancer agents.Ample evidence shows that imbalances in the gut microbiota are associated with the formation of cancer and its progression. Altering the gut microbiota via probiotics and their metabolites has gained attention among the research community as an alternative therapy to treat cancer. Probiotics exhibit health benefits as well as modulate the immunological and cellular responses in the host. Apart from probiotics, their secreted products like bacteriocins, exopolysaccharides, short-chain fatty acids, conjugated linoleic acid, peptidoglycan, and other metabolites are found to possess anticancer activity. The beneficiary role of these postbiotic compounds is widely studied for characterizing their mechanism and mode of action that reduces cancer growth. The present review mainly focuses on the postbiotic components that are employed against cancer with their reported mechanism of action. It also describes recent research works carried out so far with specific strain and anticancer activity of derived compounds both in vitro and in vivo, validating that the probiotic approach would pave an alternative way to reduce the burden of cancer.